A randomised double-blind placebo-controlled trial comparing stepwise oral misoprostol with vaginal misoprostol for induction of labour. (October 2016) - Yenuberi, Hilda; Abraham, Anuja; Sebastian, Ajit; Benjamin, Santosh J; Jeyaseelan, Visalakshi; Mathews, Jiji E
A comparison of induction of labour (IOL) using three doses of 25 µg vaginal misoprostol inserted at intervals of 4 h or more with a stepwise oral regime starting with 50 µg followed by two doses of 100 µg was studied in a double-blind placebo-controlled trial in a tertiary centre in South India. Primary outcome was vaginal delivery in 24 h. Significantly more women in the first group required oxytocin augmentation and a third dose of the drug than women in the second group. Uterine tachysystole and other maternal and neonatal complications were similar. Thus it is concluded that women induced with oral, as compared to vaginal misoprostol are more likely to labour without oxytocin.